مفاجأة الخاتمة في شعر رشيد مجيد - عارف، مصطفى لطيف; عطية، آمال مدلول (كلية العلوم الإنسانية والاجتماعية, 2023)
نحاول في بحثنا هذا أن نسلط الضوء على شعر الشاعر رشيد مجيد، وقد اخترنا من شعره زاوية تقنية محددة تتلخص في الخاتمة التي تنتهي بها قصائده، كي نتبين عن طريقها كيف يبني الشاعر قصيدته من حيث الختام، وهل تسهم تلك الخاتمة بخلق جو من التفاعل والانفعال بين النص الشعري والمتلقي، لذلك فإن أهم ما سنعمد إليه هو تحليل نماذج معينة من شعر رشيد مجيد كي نقف على أهم أساليب بناء خاتمة قصائده. In this research, we try to shed light on the poetry of the poet Rashid Majeed. We have chosen from his poetry a specific technical angle from his poetry that is summarized in the conclusion with which his poems end, in order to see through it how the poet builds his poem in terms of the conclusion, and does that conclusion contribute to Create an atmosphere of interaction and emotion between the poetic text and the recipient ;therefore, the most important thing we will do is to analyze certain models of Rashid Majeed's poetry in order to stand on the most important methods of building the conclusion of his poems.
Keywords: سعيد، رشيد مجيد، ت. 1998 م. -- الشعراء العرب -- خاتمة القصيدة -- القصائد الشعرية